PERANCANGAN APLIKASI ABSENSI KARYAWAN BERBASIS ANDROID MEMANFAATKAN API MAP BOX DENGAN METODE PROTOTYPE (STUDI KASUS PT. GLOBAL DIGITAL NIAGA) - Ramjan Agsay; Sri Mulyati (CV. Multi Kreasi Media, 2023)
PT Global Digital Niaga is engaged in online sales or E-commerce. Currently, it employs employees in all cities and regions, which have exceeded the number of +/- 3000 workers, in each branch, for example Jakarta and Tangerang, which have the highest number of employees of approximately 300 to 500 workers. . attendance system that uses finger print where there are many obstacles in doing attendance whose fingerprints are still not detected and are often constrained in queues when they want to enter the warehouse or werehouse. Even at the time of overtime there is no automatic record so that workers are required to re-absence for overtime. In the process of developing the Android-Based Employee Attendance Application Design Utilizing the Google Maps Application Programming Interface With the Prototype Method, users can take part in the development process by evaluating and providing feedback or suggestions that can be used as a reference in application development. With this research, employees who work will find it easier to do attendance because there is no need to queue again at the employee attendance machine. With this android application, it can add to the PT Global Digital Niaga brand as a provider of HR management services.